Mesenchymal stem cell–derived small extracellular vesicles (sEVs) as a therapy for sepsis-related liver injury: evidence from a systematic review and meta-analysis - Pan, Yan; Xu, Youting; Shui, Ting; Hong, Jiao; Lu, Xuan; Chen, Huilin (Frontiers in Pharmacology, 2025)
BackgroundSepsis-induced liver injury (SILI) is critical in the progression of high morbidity and mortality associated with sepsis which ends in hepatic dysfunction and multi-organ failure. Mesenchymal stem cell–derived small extracellular vesicles (MSC-sEVs) are valued for their anti-inflammatory and regenerative potential as favorable strategy. The present systematic review and meta-analysis aimed to assess the effect of MSC- sEVs in rodent models with SILI.MethodsA comprehensive systematic search was carried out in the PubMed, Web of Science, Embase, Scopus, and the Cochrane Library through April 2025. All published studies in relation to the effect of MSC- sEVs in rodent models were included. Pooled standardized mean differences (SMDs) or odds ratios (ORs) with 95% confidence intervals (CIs) were calculated for study outcomes.ResultsTen studies were included in the present study. MSC- sEVs significantly reduced ALT (SMD = −2.49, 95% CI: 3.37, −1.62), AST (SMD = −1.97, 95% CI: 3.32, −0.62), reduced pro-inflammatory cytokines (TNF-α: SMD = −5.23, 95% CI: 7.05, −3.41; IL-6: SMD = −5.00, 95% CI: 7.36, −2.64), and increased survival (OR = 6.11, 95% CI: 2.20–16.98; P = 0.001). No significant effects were observed for IL-10 (SMD = −3.39, 95% CI: 9.47, 2.69) or NLR (SMD = −0.65, 95% CI: 1.75, 0.45). Subgroup analyses illustrated that overall efficacy of treatment may vary dependent to source of sEVs, route of administration, and induction methods.ConclusionMSC- sEVs is able to improve liver function, inflammation, and survival rate in rodent sepsis model. These findings suggest that MSC- sEVs could be considered as therapeutic strategy for sepsis. These findings not only quantify the effect size of MSC- sEVs but also provide methodological insights for preclinical studies and guide future translational research.